2021
DOI: 10.1002/ps.6624
|View full text |Cite
|
Sign up to set email alerts
|

The leaf beetle Labidostomis lusitanica (Coleoptera: Chrysomelidae) as an Iberian pistachio pest: projecting risky areas

Abstract: BACKGROUND: Pistachio (Pistacia vera L.) is a commercially important tree in the Mediterranean basin, where there is a considerable increase in cultivation, especially in Spain. Because of its recent introduction as a crop in the country (1980s), studies on the pests of pistachio in Spain are still rare. Here, we studied the leaf beetle Labidostomis lusitanica (Coleoptera: Chrysomelidae), which was observed on pistachio and might become a serious pest under the expanding Spanish pistachio fields. Because early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…For instance, Rank et al [ 17 ] proposed that Lobesia botrana (Denis and Schiffermuller) and its host Vitis vinifera L. occupied a similar ecological niche, and all potential suitable cropping areas would experience the risk of being invaded by this pest. Gómez et al [ 48 ] projected at-risk areas of Labidostomis lusitanica (Germar, 1824) across pistachio cultivation at the Iberian Peninsula level and observed that this pest would find an optimal suitable climate mainly in the areas in which pistachios also had suitable climatic conditions for their growth. In the present study, only the overlapping areas of the potential distributions of M. raddei and current plantation areas or the potentially suitable regions of its susceptible hosts could be reasonably considered as risky areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Rank et al [ 17 ] proposed that Lobesia botrana (Denis and Schiffermuller) and its host Vitis vinifera L. occupied a similar ecological niche, and all potential suitable cropping areas would experience the risk of being invaded by this pest. Gómez et al [ 48 ] projected at-risk areas of Labidostomis lusitanica (Germar, 1824) across pistachio cultivation at the Iberian Peninsula level and observed that this pest would find an optimal suitable climate mainly in the areas in which pistachios also had suitable climatic conditions for their growth. In the present study, only the overlapping areas of the potential distributions of M. raddei and current plantation areas or the potentially suitable regions of its susceptible hosts could be reasonably considered as risky areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some limitations weakening the prediction of the models used here. On the one hand, it is worth noting that the MaxEnt model describes a species’ fundamental niche, rather than its realized niche, of which the prediction accuracy will be based on the quantity and quality of the presence data and the appropriateness of applied environmental factors [ 48 , 59 , 60 ]. The concealed life-history characteristic of this borer makes it more difficult to detect, especially in pest populations with low density, such as most oak forests of southern China.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, the European country with the greatest pistachio crop area, there is still a lack of knowledge on the insect pests that may threaten pistachio production [ 8 , 16 ]. Recently, a comprehensive study conducted by Gómez and coworkers highlighted the leaf beetle Labidostomis lusitanica (Germar) (Coleoptera: Chrysomelidae) as a potential serious threat for pistachio production in the Iberian Peninsula [ 17 ]. L. lusitanica is a polyphagous leaf beetle that feeds not only on pistachio, but also on Quercus L., Salix L. and Populus L., and on the herbaceous genera Rumex L. and Polygonum L. In pistachio plantations, it is considered a voracious species that may defoliate young trees in a few hours [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a comprehensive study conducted by Gómez and coworkers highlighted the leaf beetle Labidostomis lusitanica (Germar) (Coleoptera: Chrysomelidae) as a potential serious threat for pistachio production in the Iberian Peninsula [ 17 ]. L. lusitanica is a polyphagous leaf beetle that feeds not only on pistachio, but also on Quercus L., Salix L. and Populus L., and on the herbaceous genera Rumex L. and Polygonum L. In pistachio plantations, it is considered a voracious species that may defoliate young trees in a few hours [ 17 ]. The species is found mostly in the eastern and southern part of the Iberian Peninsula, overlapping with pistachio crops [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation